2007
DOI: 10.1501/sporm_0000000080
|View full text |Cite
|
Sign up to set email alerts
|

Farkli Branşlardaki̇ Sporcularin Denge Performanslarinin Karşilaştirilmasi

Abstract: ÖZETBu çalışmanın amacı: Farklı yapısal özellikler taşıyan üç ayrı spor branşının gerektirdiği denge düzeylerini tespit etmek ve branşlara göre denge performanslarını karşılaştırmaktır. Çalışmaya, halen aktif olarak spor yapan ve araştırmaya gönüllü olarak katılmayı kabul 13 basketbolcu, 9 cimnastikçi ve 13 futbolcu olmak üzere toplam 35 erkek sporcu dahil edilmiştir. Sonuç olarak: Cimnastikçilerin denge performansının basketbolculara göre daha yüksek olduğu, futbolculara göre ise sadece dinamik denge performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
2
19
0
4
Order By: Relevance
“…Aydın et al (2002), in their work with young gymnast women, they state that the gymnastist, whose eyes are open and closed, compare their ability to stand on one leg balance on a semi-hard ground, have better performance. Erkmen et al (2007) report that the highest value is; among gymnasts and footballers and the lowest value is belonging to; basketball players in their studies where they examine the balance performances of athletes dealing with different sports branches. Davlin (2004), in his study comparing the dynamic balances of elite women and men athletes doing gymnastics, swimming, football and individual sports branches, reported that the balance results of both women and men athletes in the gymnastics branch were higher than those in other branches.…”
Section: Discussionmentioning
confidence: 99%
“…Aydın et al (2002), in their work with young gymnast women, they state that the gymnastist, whose eyes are open and closed, compare their ability to stand on one leg balance on a semi-hard ground, have better performance. Erkmen et al (2007) report that the highest value is; among gymnasts and footballers and the lowest value is belonging to; basketball players in their studies where they examine the balance performances of athletes dealing with different sports branches. Davlin (2004), in his study comparing the dynamic balances of elite women and men athletes doing gymnastics, swimming, football and individual sports branches, reported that the balance results of both women and men athletes in the gymnastics branch were higher than those in other branches.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the low Y dynamic balance values obtained in our study may be due to the smaller age group. Erkmen et al (2007) compared the balance performances of athletes in different branches and found that the dynamic balance performance of gymnastics athletes was better than football players, and their static and dynamic balance performances were better than basketball athletes and its value was significant (p ≤ 0.05). In the present study, when it is compared the values of p = 0.02 and 0.00, for static and dynamic balances, respectively, significant difference was found in favor of individual athletes.…”
Section: Discussionmentioning
confidence: 99%
“…In a special position or during movement posture and balance are maintained and controlled which is fundamental for physical activity. The ability of a person to balance is described as a determinant factor for development of other motor systems (Erkmen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%